2008
DOI: 10.1007/s00223-008-9185-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bone Phenotype in ClC-7-Deficient Mice

Abstract: Mice deficient in the chloride channel ClC-7, which is likely involved in acidification of the resorption lacuna, display severe osteopetrosis. To fully characterize the osteopetrotic phenotype, the phenotypes of osteoclasts and osteoblasts were evaluated. ClC-7(-/-) mice and their corresponding wild-type littermates were killed at 4-5 weeks of age. Biochemical markers of bone resorption (CTX-I), osteoclast number (TRAP5b), and osteoblast activity (ALP) were evaluated in serum. Splenocytes were differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
9
29
1
Order By: Relevance
“…The biomarker measurements were conducted in samples from all mice, and for the samples collected during the first 12 weeks on pooled data from both experiments as described in the Methods section. doi:10.1371/journal.pone.0027482.g004 degradation markers, these data suggest that it is the remaining calcified cartilage in the bones of young osteopetrotic mice that is the basis of the poor bone strength [51]. However, the gained bone was notably devoid of woven bone, a phenomenon observed in classical osteopetrosis, and thus the increase in lamellar bone volume is likely to also contribute the increased bone strength observed in the adult osteopetrotic mice.…”
Section: Discussionmentioning
confidence: 80%
“…The biomarker measurements were conducted in samples from all mice, and for the samples collected during the first 12 weeks on pooled data from both experiments as described in the Methods section. doi:10.1371/journal.pone.0027482.g004 degradation markers, these data suggest that it is the remaining calcified cartilage in the bones of young osteopetrotic mice that is the basis of the poor bone strength [51]. However, the gained bone was notably devoid of woven bone, a phenomenon observed in classical osteopetrosis, and thus the increase in lamellar bone volume is likely to also contribute the increased bone strength observed in the adult osteopetrotic mice.…”
Section: Discussionmentioning
confidence: 80%
“…Along the same line, data from in vitro experiments show that allowing osteoclasts to resorb bone facilitates bone formation by osteoblasts in the resorbed areas (82,83). Furthermore, studies indicate that osteoclasts deposit TRACP on the bone surface leading to recruitment of osteoblasts (84), a finding that correlates with the high levels of TRACP found on the resorbed bone surfaces in ADO patients and other acid secretion-deficient systems (41,85,86) (Fig. 3).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 77%
“…Studies in the aged ovariectomized rat model using these inhibitors have shown that bone resorption is lowered, while osteoclast numbers and bone formation are maintained (63,73), thereby mimicking the phenotype of the ADO patients and ClC-7-deficient mice (11,41,85,86). Treatment with these inhibitors also resulted in increased BMD and bone strength (63,73), thereby underlining the potential of these molecules.…”
Section: Clc-7 Inhibitorsmentioning
confidence: 94%
“…Since catK is expressed primarily in osteoclasts, inhibition of this enzyme to reduce bone resorption is being explored as a pharmacologic treatment for osteoporosis. (2)(3)(4)(5)(6)(7) Recent advances have led to the discovery of drugs that selectively inhibit either acid secretion (8)(9)(10) or catK activity. (2)(3)(4)(5)11,12) Some early catK inhibitors proved to have crossreactivity with other cathepsins, (5,13,14) and cutaneous adverse events were reported for one.…”
Section: Introductionmentioning
confidence: 99%